Photodynamic therapy against cyanobacteria - Drábková, Michaela; Maršálek, Blahoslav; Admiraal, W (Environmental toxicology, 2007)
This study explores the use of photosensitizers and reactive oxygen species (ROS) to limit growth of cyanobacteria. We chose 12 phthalocyanines, tetraphenol porphyrine, and methylene blue as compounds producing singlet oxygen. Hydrogen peroxide was chosen as another source of ROS. These compounds were tested using algal toxicity tests in microplates on three cultures of green algae (Pseudokirchneriella subcapitata, Scenedesmus quadricauda, and Chlorella kessleri) and on three cultures of cyanobacteria (Synechococcus nidulans, Microcystis incerta, and Anabaena sp.). Results indicate that photosensitizers and singlet oxygen could be highly toxic for some selected phytoplankton species. Green alga Scenedesmus quadricauda was highly sensitive (EC50 = 0.07 mg/L) to compounds producing singlet oxygen, although it was not sensitive to hydrogen peroxide, which was about 10 times more toxic for cyanobacteria. We conclude that the compounds producing hydroxyl radical species seems to be more promising to treat cyanobacterial blooms than the compounds producing the singlet oxygen.
Keywords: Toxicity Tests; reaktivní formy kyslíku; fotosenzibilizující látky; Photochemistry; testy toxicity; fytoplankton; Chlorophyta; Photosensitizing Agents; fotochemie; Dose-Response Relationship, Drug; methylenová modř; Phytoplankton; financování organizované; singletový kyslík; Financing, Organized; fotochemoterapie; Methylene Blue; Reactive Oxygen Species; sinice; Porphyrins; hydroxylový radikál; peroxid vodíku; Hydroxyl Radical; Photochemotherapy; porfyriny; vztah mezi dávkou a účinkem léčiva; Singlet Oxygen; Cyanobacteria; Hydrogen Peroxide